The Rise of Anti-Asian Hate Crimes during Covid-19 Pandemic on the Discourse of Orientalism and Racial Discrimination: A Global Response - Fany Nur Rahmadiana Hakim (ISJN Journal, 2022)
COVID-19 pandemic has been impacted many aspects of people’s lives especially in social and cultural matters. Reports on hate crimes including racism, discrimination, and stigmatization continue to increase, especially those involving violence both physically and verbally. The worst incident occurred in America, with a number of reports of attacks by white Americans against Asian Americans. The rise of anti-Asian hate crimes is allegedly related to the COVID-19 pandemic. However, historically, the negative stigma against Asia has been going on for a long time due to the development of orientalism in the West. This paper examines how racial discrimination towards Asians is linked to the idea of orientalism and not only as part of the COVID-19 outbreaks. To obtain data, this paper uses publicly accessible data that has been recorded since the beginning of the pandemic and a text in social media as a trigger to be analyzed. Using literature review and discourse analysis, this paper will focus on the dynamics of orientalism in the Western World and the rise of Anti-Asian hate crimes in COVID-19. Study found that the internalized orientalism is still attached to Western people and it causing some of them to perpetrate racial discriminatory behavior and hate crimes toward Asians. This paper also includes the global response to Anti-Asian hate crimes that occurred in several Western countries during the pandemic of COVID-19 especially in rising awareness on ceasing racial discrimination.